The effects of viewing forests with different planting densities on physiological and psychological responses: A between-subject experiment - Jittakon Ramanpong; Jie Yin; Chen-Jia Zhang; Huan-Tsun Chen; Ming-Jer Tsai; John D. Spengler; Chia-Pin Yu (Trees, Forests and People, 2024)
Beyond their traditional role in timber production, plantation forests are increasingly recognized for their therapeutic potential. Forest management practices allow for modifications to meet diverse demands, making it crucial to understand the association between stand density and human responses. This knowledge is essential for forest therapy practitioners and landscape designers aiming to maximize the therapeutic effects of these landscapes. This article delves into the effects of viewing forest plantations on health responses, exploring whether different planting densities influence human physiological and psychological reactions. To investigate this, we conducted a between-subject, pretest-posttest field experiment in three plantation forests with varying stand densities (high, medium, and low), using a parking area as a control. Our findings revealed that viewing plantation forests led to both physiological and psychological relaxation effects. Notably, medium-density plantation forests with a 3-meter spacing between trees, demonstrated a more significant relaxation effect on reducing heart rate compared to high and low-density plantations with spacing of 1 m and 5 m, respectively. High-density plantation forests were more effective in reducing total mood disturbance and specific negative mood states, including fatigue-inertia, depression-dejection, and tension-anxiety. Interestingly, regardless of stand density, restorative components were similar among the four experimental settings (high, medium, low, and control). These findings have practical implications for designing restorative environments and leveraging the therapeutic potential of plantation forests.